2019
DOI: 10.12688/f1000research.16890.1
|View full text |Cite
|
Sign up to set email alerts
|

Association between +45T>G adiponectin polymorphism gene and type 2 diabetes mellitus and metabolic syndrome in a Venezuelan population

Abstract: Background: Adiponectin (ADIPOQ) is a hormone primarily synthesized by adipocytes and encoded by the ADIPOQ gene, which exerts anti-inflammatory, antiatheratogenic and insulin sensitizing functions. It has been shown that its plasma concentrations are decreased in individuals with metabolic syndrome (MS) and type 2 diabetes mellitus (DM2), which could be due to variations in the gene coding for this protein. The aim of this study was to detect the +45 T>G polymorphism of the ADIPOQ gene in subjects with DM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Although, without difference in the frequency of MS, the TT + TG SCT group may present a higher risk of worsening in the long-term cardiometabolic profile, and even of MS. On the other hand, Sanchés et al. [ 28 ] suggested that the presence of the G allele has a protective effect in individuals with DM2 and MS. In a previous study, Retamoso et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although, without difference in the frequency of MS, the TT + TG SCT group may present a higher risk of worsening in the long-term cardiometabolic profile, and even of MS. On the other hand, Sanchés et al. [ 28 ] suggested that the presence of the G allele has a protective effect in individuals with DM2 and MS. In a previous study, Retamoso et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the expression pattern of adiponectin can be severely affected by single nucleotide polymorphisms (SNPs) in the ADIPOQ gene (Enns et al, 2011), such as -11391G>A (rs17300539), -11377C>G (rs266729), +45T>G (rs2241766), and +276G>T(rs1501299), all of which have been associated with high Body Mass Index (BMI), high blood glucose levels, increased T2D risk, obesity, and metabolic syndrome (Enns et al, 2011;Sanchez et al, 2019;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%